Making a nation: The colonial university as contact zone in the novels of Adibah Amin - Ahmad, Siti Nuraishah (2017)
In the 1950s, cities such as Singapore, Johor Bahru, and Kuala Lumpur were sites of intellectual and political ferment as Malaya and Singapore moved towards independence from British rule. Along with the struggle for independence, notions of identity, nation and belonging were also being played out in the cities, as the various ethnic communities remained divided. The Malaysian writer Adibah Amin (1936 - ) explores these issues in two of her novels, Tempat Jatuh Lagi Dikenang (1983) and This End of the Rainbow (2006), from the point-of-view of a young, female, Malay student in Singapore in the early ‘50s. This paper thus examines the city in Adibah’s novels as a site where competing visions of a future post-colonial nation are laid out and debated, and how the conflicts in the novels reveal the role of discourses on ‘race’ and identity in imagining the nation. Of particular interest is Adibah’s depiction of the university as a contact zone where young Malayans challenge colonialism and imagine a future nation whose members enjoy equal rights.